1999
DOI: 10.1097/00006534-199901000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Adhesion Formation by a Single Application of 5-Fluorouracil after Flexor Tendon Injury

Abstract: Using an animal model, the effect of a single intraoperative application of 5-fluorouracil on digital flexor tendon adhesions was assessed. After a standard partial division of the tendon and immobilization with a stitch, the synovial sheath in 30 rabbit tendons was treated with 5-fluorouracil solution (50 mg/ml)-soaked sponge pledgets for 5 minutes. Buffered saline was substituted for 5-fluorouracil in 30 control tendons. The tendons were harvested 1 week postoperatively, and histologic sections were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 21 publications
0
48
0
Order By: Relevance
“…6 It is therefore considered that if an intrinsic response could be stimulated at the early stage of tendon healing, the outcome of tendon repair would be preferable with regard to reducing peritendinous adhesion. Based on this idea, a wide range of substances, including fibrin sealant, 11 5-fluorouracil, 12 sodium hyaluronate, 15 aprotinin, 16 and TGF-␤1 neutralizing antibody, 17 have been experimentally applied to the tendon repair, with the aim of reducing extrinsic healing and stimulating the intrinsic mechanism. However, problems such as high cost of raw materials, potential side effects, and limited bioavailability have prevented widespread clinical use of these agents.…”
Section: Discussionmentioning
confidence: 99%
“…6 It is therefore considered that if an intrinsic response could be stimulated at the early stage of tendon healing, the outcome of tendon repair would be preferable with regard to reducing peritendinous adhesion. Based on this idea, a wide range of substances, including fibrin sealant, 11 5-fluorouracil, 12 sodium hyaluronate, 15 aprotinin, 16 and TGF-␤1 neutralizing antibody, 17 have been experimentally applied to the tendon repair, with the aim of reducing extrinsic healing and stimulating the intrinsic mechanism. However, problems such as high cost of raw materials, potential side effects, and limited bioavailability have prevented widespread clinical use of these agents.…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in the surgical techniques and postoperative management, difficulties with tendon repair (delayed return of tendon strength for approximately 3 weeks following repair, gap formation, longitudinal fibre orientation complicating sutureholding, adhesion formation) are faced. Furthermore, tendon repair encounters technical (essentially physical problems) and biological (concerns primarily with vascularisation and peri-tendinous fibrosis causing adhesion formation) issues (Akali et al, 1999;Jaibaji, 2000;Ferguson & Rinker, 2006;Temizet al, 2008;Mousavi et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Restrictive adhesion and local inflammation can be modulated by using this simple technique. 11,12,34) In a rabbit flexor tendon injury model, Bates et al 9) observed that a single intraoperative dose of mannose-6-phosphate, a natural inhibitor of transforming growth factor-beta, enhanced the postoperative range of motion. Adcon gel provides a physical barrier to inter-tissue adhesions and inhibits fibroblast migration on and around neural and tendinous structures and prevents adhesion formation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous materials and agents have been used as a mechanical barrier to envelop sutured tendons in attempts to minimize the adhesion formation after primary tendon repair. Currently, the modalities used for preventing adhesions without affecting the healing process include; human amniotic fluid, hyaluronic acid, alginate solution, mannose-6-phosphate, 5-fluorouracil, injection of growth factors or platelet concentrate, local application of extracorporeal shock wave therapy or ultrasound therapy, local injection of bone-marrow-derived mesenchymal stem cells, systemic administration of antiinflammatory drugs [7][8][9][10][11][12][13][14][15][16] . The use of a barrier during surgery to protect raw tissue surfaces has been shown to be one of the most effective methods of preventing tendon adhesions.…”
Section: Introductionmentioning
confidence: 99%